Reconstructing historic Glacial Lake Outburst Floods through numerical modelling and geomorphological assessment: Extreme events in the Himalaya. Issue 12 (30th July 2014) - Westoby, Matthew J.; Glasser, Neil F.; Hambrey, Michael J.; Brasington, James; Reynolds, John M.; Hassan, Mohamed A. A. M.
ABSTRACT Recession of high‐mountain glaciers in response to climatic change frequently results in the development of moraine‐dammed glacial lakes. Moraine dam failure is often accompanied by the release of large volumes of water and sediment, termed a Glacial Lake Outburst Flood (GLOF). Chukhung Glacier is a small ( 3 km2) receding valley glacier in Mt. Everest (Sagarmatha) National Park, Nepal. Unlike many Himalayan glaciers, which possess a thick mantle of supraglacial debris, its surface is relatively clean. The glacier terminus has receded 1.3 km from its maximum Holocene position, and in doing so provided the space for an ice‐contact moraine‐dammed lake to develop. The lake had a maximum volume of 5.5 × 105 m3 and drained as a result of breaching of the terminal moraine. An estimated 1.3 × 105 m3 of material was removed from the terminal moraine during breach development. Numerical dam‐breach modelling, implemented within a Generalised Likelihood Uncertainty Estimation (GLUE) framework, was used to investigate a range of moraine‐dam failure scenarios. Reconstructed outflow peak discharges, including failure via overtopping and piping mechanisms, are in the range 146–2200 m3 s‐1. Results from two‐dimensional hydrodynamic GLOF modelling indicate that maximum local flow depths may have exceeded 9 m, with maximum flow velocities exceeding 20 m s‐1 within 700 m of the breach. The floodwaters mobilised a significant amount of material, sourced mostly from the expanding breach, forming a 300 m long and 100 m wide debris fan originating at the breach exit. moraine‐dam. These results also suggest that inundation of the entire floodplain may have been achieved within ten minutes of initial breach development, suggesting that debris fan development was rapid. We discuss the key glaciological and geomorphological factors that have determined the evolution of a hazardous moraine‐dammed lake complex and the subsequent generation of a GLOF and its geomorphological impact. © 2014 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd.